2012
DOI: 10.1038/tp.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of bumetanide in the treatment of autism in children

Abstract: Gamma aminobutyric acid (GABA)-mediated synapses and the oscillations they orchestrate are altered in autism. GABA-acting benzodiazepines exert in some patients with autism paradoxical effects, raising the possibility that like in epilepsies, GABA excites neurons because of elevated intracellular concentrations of chloride. Following a successful pilot study,1 we have now performed a double-blind clinical trial using the diuretic, chloride-importer antagonist bumetanide that reduces intracellular chloride rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
229
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(242 citation statements)
references
References 85 publications
11
229
0
2
Order By: Relevance
“…Data are represented as mean ± SEM *P < 0.05, **P < 0.01, ***P < 0.001, determined by one-way ANOVA with Bonferroni correction. (42,43). NKCC1 also interacts with DISC1 to regulate the risk of schizophrenia (44).…”
Section: Discussionmentioning
confidence: 99%
“…Data are represented as mean ± SEM *P < 0.05, **P < 0.01, ***P < 0.001, determined by one-way ANOVA with Bonferroni correction. (42,43). NKCC1 also interacts with DISC1 to regulate the risk of schizophrenia (44).…”
Section: Discussionmentioning
confidence: 99%
“…A disturbance in GABAergic function at this stage causes neurodevelopmental disorders, such as mental retardation, Angelman syndrome, epilepsy, and autism (21). Recently, bumetanide has been shown to improve behavior in children with autism by reducing GABAergic excitation (22). GABA also acts as an excitatory neurotransmitter in the mature but pathological brain (23).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study done on 60 children showed improvements in some ASD‐related clinical manifestations. Therefore, bumetanide is currently under investigation as a prospective drug by restoring the gradient and GABA inhibition and, thereby, considered as a potential ASD‐therapeutic agent (Lemonnier et al., 2012; Table 3). …”
Section: Reviewmentioning
confidence: 99%